2018
DOI: 10.1016/j.lwt.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Production, characterization and In vitro antioxidant activities of exopolysaccharide from Weissella cibaria GA44

Abstract: Exopolysaccharide (EPS) producing lactic acid bacteria (LAB) strain GA44 isolated from gari (a Nigerian traditional fermented cassava mash) was identified with 16S rRNA gene sequencing as Weissella cibaria. The EPS produced mainly composed of glucose and rhamnose sugar units and its molecular mass was about 2.8 Â 10 5 Da. The fourier-transform infrared (FT-IR) spectrum analysis showed characteristics absorption peaks indicating the presence of eOH, C¼O and C-H groups. Central composite design (CCD) and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 44 publications
5
55
0
2
Order By: Relevance
“…These results were in agreement with the previously observed structural diversity of EPS produced by LAB (Zeidan et al, 2017), confirming that galactose and glucose, and to a lesser extent mannose and rhamnose, are the most frequently occurring sugars in EPS produced by lactobacilli. The EPS produced by W4451 were characterized by a composition similar to the HePS produced by W. cibaria (Adesulu-Dahunsi et al, 2018) but different from other Weissella species' EPS (Bejar et al, 2013;Adesulu-Dahunsi et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…These results were in agreement with the previously observed structural diversity of EPS produced by LAB (Zeidan et al, 2017), confirming that galactose and glucose, and to a lesser extent mannose and rhamnose, are the most frequently occurring sugars in EPS produced by lactobacilli. The EPS produced by W4451 were characterized by a composition similar to the HePS produced by W. cibaria (Adesulu-Dahunsi et al, 2018) but different from other Weissella species' EPS (Bejar et al, 2013;Adesulu-Dahunsi et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…At 0.2 mg/ml, the purified EPS had scavenging activity of 14.74 ± 1.02%, but increased drastically to 76.75 ± 3.02% at 5 mg/ml, approaching that (90.08 ± 2.08%) of Vc at the same concentration. In comparison, the EPSs produced by Enterococcus faecium BDU7 and Weissella cibaria GA44 had much lower DPPH RSA, being 63.5% at 10 mg/ml and 48.9% at 4 mg/ml, respectively [44,45]. The relatively potent scavenging activity on DPPH radical of the EPS might be due to its relatively lower molecular weight (54 kDa).…”
Section: Antioxidant Propertiesmentioning
confidence: 96%
“…This indicates that LAP1 was able to utilise sucrose added to the medium as carbon source for the synthesis of EPS. EPS producing ability of Weissella sp have been previously reported by several researchers (Adesulu-Dahunsi et al, 2018;Yu et al, 2018). Tang et al (2018) reported improvement in Chinese steamed bread quality due to in situ exopolysaccharide produced by Weissella confusa QS813.…”
Section: Organic Acid Productionmentioning
confidence: 79%